A Novice Teacher’s Familiarity with Assessment for Learning in EFL Classroom - Endang Setyaningsih; Sumardi Sumardi; Ni'matul Farikhah (Universitas Hamzanwadi, 2022)
This case study aims to find out a novice teacher's knowledge of assessment for learning (AFL) and which AFL strategies are frequently used and considered helpful to enhance students' English proficiency. This study digs into the experience of an English teacher who has been teaching for two years in a secondary school in South Sumatra, Indonesia. The data of the study were mainly obtained from interviews and teaching artifacts. The collected data were then analyzed using thematic analysis. The study revealed that the teacher’s understanding of AFL is sufficient to implement AFL. On the other hand, support from the principal, fellow teachers, and students for the teacher to conduct the AFL was perceived as lacking. Despite the limitations, the teacher reported an attempt to conduct AFL using several strategies. Sharing learning intentions and success criteria with students, asking questions, and classroom discussion are among the strategies that are considered helpful. In contrast, teacher feedback and self and peer assessment are considered less effective. The findings imply a lack of teachers’ professional competence, particularly in conducting AFL. Suggestions are drawn to address the issues.